2015
DOI: 10.1037/ort0000061
|View full text |Cite
|
Sign up to set email alerts
|

Asylum-seeking children’s experiences of detention in Canada: A qualitative study.

Abstract: Children and parents seeking asylum are regularly detained in Canada, however little is known about the experiences of detained families. International literature suggests that the detention of children is associated with significant morbidity. Our study aims to understand the experiences of detained children and families who have sought asylum in Canada by using a qualitative methodology that includes semistructured interviews and ethnographic participant observation. Detention appears to be a frightening exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 22 publications
2
43
0
5
Order By: Relevance
“…Our studies have shown that detention negatively impacts the mental health of both adults (Cleveland & Rousseau, 2013) and children (Kronick et al, 2015;Kronick, Rousseau, & Cleveland, 2016;. These findings are consistent with studies conducted in multiple other countries (Bosworth, 2016).…”
Section: Symbolic Violence Disempowerment and Mental Healthsupporting
confidence: 90%
“…Our studies have shown that detention negatively impacts the mental health of both adults (Cleveland & Rousseau, 2013) and children (Kronick et al, 2015;Kronick, Rousseau, & Cleveland, 2016;. These findings are consistent with studies conducted in multiple other countries (Bosworth, 2016).…”
Section: Symbolic Violence Disempowerment and Mental Healthsupporting
confidence: 90%
“…62 -66 Detention itself undermines parental authority and capacity to respond to their children's needs; this difficulty is complicated by parental mental health problems. 56,67 Although data are limited regarding the effects of a short detention time on the health of children, there is no evidence indicating that any time in detention is safe for children.…”
Section: Impact Of Detention On Child and Family Healthmentioning
confidence: 99%
“…54 Studies of detained immigrants, primarily from abroad, have found negative physical and emotional symptoms among detained children, 55 -57 and posttraumatic symptoms do not always disappear at the time of release. 56 Young detainees may experience developmental delay 58 and poor psychological adjustment, potentially affecting functioning in school. 59 Qualitative reports about detained unaccompanied immigrant children in the United States found high rates of posttraumatic stress disorder, anxiety, depression, suicidal ideation, and other behavioral problems.…”
Section: Impact Of Detention On Child and Family Healthmentioning
confidence: 99%
“…The family spent three years in a United Nations High Commissioner for Refugees refugee camp in Jordan and is now in Canada as part of a humanitarian resettlement program (Box 1). [1][2][3][4][5][6][7] Fatima is 28, Omar is 32, and Ruya (which means "vision" or "dream" in Arabic) is 4 years old. They have no health or immunization records with them.…”
mentioning
confidence: 99%